Integrating Smart Health Informatics with Community Health Education: A Predictive Diagnosis Framework for Rural U.S. Communities - Nilima, Sadia Islam; Tasnim, Afia Fairooz; Semi, Mst Masuma Akter; Rahman, Rukshanda; Yeasmin, Sumaiya; Dhar, Sweety Rani; Alam, Mohammad Zahidul; Kamal, Md Bayzid (Journal of Posthumanism, 2023)
This study presents a smart predictive healthcare framework tailored to support individuals in the United States living with chronic conditions, especially those receiving care at home. The framework incorporates a deep learning model that analyzes large volumes of patient data, including vital signs, physical activity, medication usage, and symptoms. These data are collected through ambient assisted living technologies. The model is part of an intelligent module that operates at the patient’s location to deliver accurate health status predictions and personalized care recommendations. The framework was tested using data from patients with chronic blood pressure conditions, collected every 15 minutes over one year. The proposed model achieved a prediction accuracy of approximately 97.6% % outperforming a standard baseline model by nearly 6%. Additionally, improvements in identifying critical health events were observed, with the F score increasing by 9% for hypertensive, 26% for hypotensive, and 10% for normotensive cases. These results demonstrate the model’s effectiveness in detecting early warning signs and enhancing the management of chronic diseases. The framework shows strong potential for improving healthcare access and reducing emergency risks in rural and underserved communities across the United States.